ANALISIS MOTIVASI SISWA DALAM MENGIKUTI EKSTRAKURIKULER SENAM DI KELAS VIII UPT SMP 025 SIBORUTOROP PANRIBUAN TAHUN 2025 - Nainggolan, Aser Paul; Widya, Tri; Ginting, Yabes; Br. Perangin-angin, Hellinika (Jurnal Ilmiah Aquinas, 2025)
Nowadays, gymnastics has received considerable attention both to improve the quality of human beings in terms of physical fitness and to improve achievement. One of the places where students do gymnastics and arts activities is at school, a place of study, and do gymnastics activities outside of school hours, namely by doing extracurricular activities. Gymnastics and arts activities in the country still require special attention and guidance, both in an effort to find new seeds and an effort to improve athlete achievement. Based on observations, information was obtained that students prefer gymnastics extracurricular activities more than non-gymnastics extracurricular activities. Many students at UPT SMP 025 Siborutorop are interested in gymnastics extracurricular activities, because gymnastics extracurricular activities are activities carried out outside of school hours which are useful for improving the quality of physical fitness, gymnastics requires teenagers (students) to move dynamically and have good physical behavior to do it, besides it is useful for applying knowledge values, expanding horizons and gymnastics abilities. Most consider extracurricular programs to be a way to fill free time to refresh and make the body healthy. This is not quite right, because by following extracurricular activities the body becomes healthy and gains knowledge about gymnastics. Where gymnastics extracurricular enthusiasts are greater than non-gymnastic extracurricular. Based on the description and explanation in the background above, the author is interested in conducting a study entitled "Analysis of Student Motivation in Participating in Gymnastics Extracurricular in Class VIII UPT SMP 025 Siborutorop Panribuan in 2025". The data analysis technique used in this study was descriptive quantitative. Data were obtained by distributing motivation questionnaires to students, which were arranged in the form of a Likert scale with five alternative answers, namely: Strongly Agree (SS) given a score of 5, Agree (S) score 4, Undecided (R) score 3, Disagree (TS) score 2, and Strongly Disagree (STS) score 1. Based on the results of the study, it showed that student motivation in gymnastics extracurricular activities at UPT SMP 025 Siborutorop was high. In detail, there are 7 students (23%) who have low motivation, 5 students (16%) who have moderate motivation, and 18 students (60%) who have very high motivation. The Frequency Percentage Category Interval can be described as follows; 1. X > 60% Very High 2. X > 16% Moderate 3. X> 23% Low.